2015
DOI: 10.1038/ncomms8151
|View full text |Cite
|
Sign up to set email alerts
|

The oncogenic microRNA miR-21 promotes regulated necrosis in mice

Abstract: MicroRNAs (miRNAs) regulate apoptosis, yet their role in regulated necrosis remains unknown. miR-21 is overexpressed in nearly all human cancer types and its role as an oncogene is suggested to largely depend on its anti-apoptotic action. Here we show that miR-21 is overexpressed in a murine model of acute pancreatitis, a pathologic condition involving RIP3-dependent regulated necrosis (necroptosis). Therefore, we investigate the role of miR-21 in acute pancreatitis injury and necroptosis. miR-21 deficiency pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
74
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(81 citation statements)
references
References 46 publications
7
74
0
Order By: Relevance
“…Kuśnierz-Cabala B et al demonstrated that the expression levels of miR-126-5p, miR-148a-3p, miR-216a-5p, miR-551b-5p and miR-375 were significantly elevated in moderate and severe acute pancreatitis (SAP) when compared to control subjects; however, in mild acute pancreatitis (MAP) patients, only miR-216a-5p, miR-551b-5p, and miR-375 were highly expressed [13]. Ma X et al reported that miR-21 was overexpressed in a murine model of AP [14], and An F et al discovered that miR-24-3p, miR-361-5p, miR-1246 and miR-222-3p were constantly up-regulated, and miR-181a-5p was constantly down-regulated, in hypertriglyceridemia-induced acute pancreatitis patients [15]. Moreover, it has been reported that miR-375, miR-217, miR-148a, miR-216a, miR-122, miR-214 and miR-138 were increased in mesenteric lymph nodes from rats with AP, and miR-217, miR-375, miR-122 and miR-148a were also increased in matched rat plasma samples [16].…”
Section: Introductionmentioning
confidence: 99%
“…Kuśnierz-Cabala B et al demonstrated that the expression levels of miR-126-5p, miR-148a-3p, miR-216a-5p, miR-551b-5p and miR-375 were significantly elevated in moderate and severe acute pancreatitis (SAP) when compared to control subjects; however, in mild acute pancreatitis (MAP) patients, only miR-216a-5p, miR-551b-5p, and miR-375 were highly expressed [13]. Ma X et al reported that miR-21 was overexpressed in a murine model of AP [14], and An F et al discovered that miR-24-3p, miR-361-5p, miR-1246 and miR-222-3p were constantly up-regulated, and miR-181a-5p was constantly down-regulated, in hypertriglyceridemia-induced acute pancreatitis patients [15]. Moreover, it has been reported that miR-375, miR-217, miR-148a, miR-216a, miR-122, miR-214 and miR-138 were increased in mesenteric lymph nodes from rats with AP, and miR-217, miR-375, miR-122 and miR-148a were also increased in matched rat plasma samples [16].…”
Section: Introductionmentioning
confidence: 99%
“…While apoptosis is considered to be rather immunosuppressive, necroptosis has been suggested to be proinflammatory and to initiate inflammation. Accordingly, studies implicated necroptosis in the pathogenesis of several inflammatory diseases, such as inflammatory bowel disease and kidney diseases (8,(12)(13)(14). Conversely, the role of programmed necrotic cell death in human inflammatory liver diseases still remains to be fully elucidated (15).…”
Section: Introductionmentioning
confidence: 99%
“…High miR-21 levels are, therefore, considered to be a marker of immune cell activation (7). Regarding pathological necrosis, miR-21 enhances cellular necrosis by negatively regulating tumor suppressor genes associated with the death receptor-mediated intrinsic apoptotic pathway (8).…”
Section: Introductionmentioning
confidence: 99%